2000
DOI: 10.1046/j.1365-2389.2000.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in organic matter, nitrogen, phosphorus and cations in soil as a result of fire and water erosion in a Mediterranean landscape

Abstract: Summary Fire affects large parts of the dry Mediterranean shrubland, resulting in erosion and losses of plant nutrients. We have attempted to measure these effects experimentally on a calcareous hillside representative of such shrubland. Experimental fires were made on plots (4 m × 20 m) in which the fuel was controlled to obtain two different fire intensities giving means of soil surface temperature of 439°C and 232°C with temperatures exceeding 100°C lasting for 36 min and 17 min. The immediate and subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 13 publications
7
71
1
5
Order By: Relevance
“…As for C, stabilisation treatments had little effect on sediment N concentration, as also indicated Thomas et al (2000) for a litter treatment, lowest values being observed with mulching. Accumulated losses of N in seeding and control plots largely exceeded the usual range in burnt soils (14-57kgha~1 year -1 : Debano andConrad 1978: Helvey et al 1985;Soto et al 1997;Baird et al 1999;Thomas et al 1999;Gimeno-Garcia et al 2000;Lane et al 2008), being only below the highest values reported for high severity wildfires (100-129kg ha -1 : SotoefaZ. 1997; Spigel and Robichaud 2007); with mulching the mass of total N eroded was only half of the lowest values.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…As for C, stabilisation treatments had little effect on sediment N concentration, as also indicated Thomas et al (2000) for a litter treatment, lowest values being observed with mulching. Accumulated losses of N in seeding and control plots largely exceeded the usual range in burnt soils (14-57kgha~1 year -1 : Debano andConrad 1978: Helvey et al 1985;Soto et al 1997;Baird et al 1999;Thomas et al 1999;Gimeno-Garcia et al 2000;Lane et al 2008), being only below the highest values reported for high severity wildfires (100-129kg ha -1 : SotoefaZ. 1997; Spigel and Robichaud 2007); with mulching the mass of total N eroded was only half of the lowest values.…”
Section: Discussionmentioning
confidence: 82%
“…Stabilisation treatments had small effects on sediment C concentration, with the lowest values in mulching plots. Except for with mulching, the accumulated amount of C in the sediments was 5-fold those after high and moderate intensity experimental fires in eastern Spain (Gimeno-Garcia et al 2000) and it slightly exceeded the highest value (900kgha _1 ) observed the first year after high severity wildfires (Baird et al 1999;Spigel and Robichaud 2007). This result suggested that, whereas low intensity prescribed fires reduce nutrient losses by volatilisation relative to wildfires, they expose available nutrients to erosion (de Koff et al 2006).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The temperatures on the soil surface and their duration were measured in 1995, and also in 2003 fires by means of thermosensitive paints and thermocouples (Gimeno-García et al, 2007). In 1995, statistically significant differences, between T1 and T2, were observed on the average soil surface temperatures (439ºC and 232ºC, respectively) and on the average values of residence time in soil of temperatures greater than 100ºC (36 minutes in T1 and 17 minutes in T2) (Gimeno-García et al, 2000, 2004.…”
Section: Fire Experimental History and Designmentioning
confidence: 99%